The Pastoral Origin of Semiotically Functional Tonal Organization of Music - Nikolsky, Aleksey (Frontiers in Psychology, 2020)
This paper presents a new line of inquiry into when and how music as a semiotic system was born. Ten principal expressive aspects of music retain specific structural patterns to signify a certain affective state, which distinguishes the tonal organization of music from the phonetic and prosodic organization of natural languages. Therefore, the question of music’s origin can be answered by establishing the point in human history, at which expressive aspects might have been abstracted from the instinct-driven primate calls and used to express human psycho-emotional states. Etic analysis of acoustic parameters is the prime means of cross-comparison of the typical patterns of expression of the same basic emotions in human music versus animal vocal communication. A new method of such analysis is proposed here. Formation of such expressive aspects as meter, tempo, melodic intervals, and articulation can be explained by the influence of bipedal locomotion, breathing cycle, and heartbeat, long before Homo sapiens. However, two aspects, rhythm and melodic contour, most crucial for music as we know it, lack proxies in the Paleolithic lifestyle. The available ethnographic and developmental data leads one to believe that rhythmic and directional patterns of melody became involved in conveying emotion-related information as a result of frequent switching from one call-type to another within the limited repertory of calls adopted for ongoing caretaking of human youngsters and domestic animals. The efficacy of rhythm and pitch contour in affective communication must have been discovered spontaneously in new important cultural activities. The most likely scenario for music to have become fully semiotically functional is the formation of cross-specific communication between humans and domesticated animals during the Neolithic demographic explosion. The model of such communication can be found in the surviving tradition of Scandinavian pastoral music. This article discusses the most likely ways in which such music evolved.